OSNA-Assisted Molecular Staging in Colorectal Cancer: A Prospective Multicenter Trial in Japan - Yamamoto, Hirofumi; Tomita, Naohiro; Inomata, Masafumi; Furuhata, Tomohisa; Miyake, Yasuhiro; Noura, Shingo; Kato, Takeshi; Murata, Kohei; Hayashi, Shigeoki; Igarashi, Seiji; Itabashi, Michio; Kameoka, Shingo; et al. (Annals of surgical oncology, 2016)
Background We previously reported that the one-step nucleic acid amplification (OSNA) assay provided a judgment performance for colorectal cancer equivalent to a 2-mm-interval histopathological examination of lymph nodes (concordance 97.1 %, n = 385 lymph nodes). In this prospective multicenter study, we uncovered an OSNA-assisted pathology to detect lymph node metastasis. Methods A total of 204 (50 stage I, 74 stage II, and 80 stage III) colorectal cancer patients. All 4324 lymph nodes were examined by the standard histology (one-slice H&E staining) and 1925 lymph nodes (44.5 %) of them were also subject to the OSNA analysis. Results The concordance rate between 1 slice hematoxylin/eosin and OSNA assay was 95.7 % (1,842/1925 lymph nodes). The sensitivity and specificity of the OSNA assay were 86.2 % (125/145) and 96.5 % (1717/1780), respectively. Among 124 node-negative patients (pN0), the respective upstaging rates of pStages I, IIA, IIB, and IIC were 2.0 % (1/50), 17.7 % (11/62), 12.5 % (1/8), and 25 % (1/4). OSNA-positive patients had deeper invasion to the colonic wall and severe lymphatic invasion ( P = 0.048 and P = 0.004, respectively). The sum of the quantitative results of OSNA and total tumor load increased as the number of metastasized lymph nodes increased: 1550 copies/μL in pN0, 24,050 copies/μL in pN1, and 90,600 copies/μL in pN2. Conclusions The present study on colorectal cancer provided fundamental data regarding OSNA-assisted pathology of lymph node metastasis in Japan.